Environment‐tolerant conductive and superhydrophobic poly(m‐phenylene isophthalamide) fabric prepared via γ‐ray activation and reduced graphene oxide/nano SiO2 modification. Issue 16 (6th December 2021) - Li, Taolin; Zou, Lin; Cheng, Kaichang; Liu, Xiang; Shi, Honghui; Yang, Qingqing; Chang, Baobao; Shi, Xianzhang; Ma, Jialu; Liu, Chuntai; Shen, Changyu
Abstract: As one of the high‐performance polymer fibers, poly(m‐phenylene isophthalamide) (PMIA) is widely used in the area of military and aerospace applications. Whereas, its insulation and hydrophilic nature may lead to electric charge accumulation and dust adherence. This work aims to fabricate a PMIA fabric with integrated conductive and superhydrophobic abilities via a simple method including γ‐ray irradiation and dip‐coating. Results show that after γ‐ray irradiation, the surface roughness of PMIA was enhanced and the content of the oxygen element was increased. In the dip‐coating step, the micro‐pits and grooves on the surface of PMIA were covered totally by a layer of graphene oxide (GO). After reduction to reduced GO (rGO), a conductive network was built. The conductivity of the fabric was decreased to a minimum value of 0.5 Ω m. Meanwhile, the quite low volume resistivity was retained as 1H, 1H, 2H, 2H‐perfluorooctyltriethoxysilane (PFTS)/hydrophobic fumed silica nanoparticles (SiO2 ) was decorated on rGO. Due to the microscale aggregation constituted by nano‐SiO2, the fabric presented a superhydrophobic property and self‐cleaning ability against simulated Lunar dust. Furthermore, the durability performance proves that an excellent environment‐tolerant ability has been endowed to the PMIA fabric by the modification. Abstract : Poly(m‐phenylene isophthalamide) (PMIA) fabric with integrated conductive and superhydrophobic abilities via a simple method including γ‐ray irradiation and dip‐coating was fabricated. The surface roughness of PMIA was enhanced and the content of the oxygen element was increased after γ‐ray irradiation, benefiting greatly the decorating of graphene oxide and silica nanoparticles. The conductivity and superhydrophobic ability were realized by the reduction of graphene oxide and microscale aggregation of silica nanoparticles.